(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The research aims to determine the effect of work conflict, work stress, and workload on job satisfaction of employees with work motivation as an intervening variable at the personnel agency and human resource development of Sungai Penuh City. The subjects of this research are employees of the BKPSDM of Sungai Penuh City. The type of research used in this study is causal quantitative research, and the data collection method is through distributing questionnaires. The sampling technique used in this research is saturation sampling by analyzing 53 respondents. The analysis technique used is multiple linear regression analysis with the assistance of the SmartPLS program. Based on the results of the analysis, it can be concluded that work conflicts significantly affect work motivation. Work stress does not significantly affect work motivation. Workload significantly affects work motivation. Work conflicts do not significantly affect job satisfaction. Work stress does not significantly affect job satisfaction. Workload significantly affects job satisfaction. Work motivation significantly affects job satisfaction. Work motivation is able to mediate the effect of work conflicts on job satisfaction. Work motivation is unable to mediate the effect of work stress on job satisfaction. Work motivation is able to mediate the effect of workload on job satisfaction.